2021
DOI: 10.1186/s12888-020-02981-7
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment rate, opioids misuse and other substance abuse: quasi-experimental evidence from treatment admissions data

Abstract: Background The relationship between economic conditions and substance abuse is unclear, with few studies reporting drug-specific substance abuse. The present study examined the association between economic conditions and drug-specific substance abuse admissions. Methods State annual administrative data were drawn from the 1993–2016 Treatment Episode Data Set. The outcome variable was state-level aggregate number of treatment admissions for six cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
(26 reference statements)
2
16
1
Order By: Relevance
“…Including nationally representative data, the Drug and Alcohol Services Information System has documented low employment rates among adult individuals undergoing SUD treatment: less than onethird of the sample (31%) were employed (Substance Abuse and Mental Health Services Administration Office of Applied Studies, 2008). A recent experimental study on the economic condition and admission among patients with SUD has concluded that economic hardship may increase the number of SUD admissions (Azagba et al, 2021). The coronavirus disease (COVID-19) pandemic resulted in economic downturns worldwide, including in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Including nationally representative data, the Drug and Alcohol Services Information System has documented low employment rates among adult individuals undergoing SUD treatment: less than onethird of the sample (31%) were employed (Substance Abuse and Mental Health Services Administration Office of Applied Studies, 2008). A recent experimental study on the economic condition and admission among patients with SUD has concluded that economic hardship may increase the number of SUD admissions (Azagba et al, 2021). The coronavirus disease (COVID-19) pandemic resulted in economic downturns worldwide, including in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…We tested whether the association between health insurance and heaving-drinking rates differed between economic downturns and upturns. Following previous studies, we replaced health insurance variables in Model 1 with two decomposed variables – insurance coverage during economic downturns and insurance coverage during economic upturns -- in order to capture potential asymmetric effects ( Azagba et al, 2021 , Carpenter et al, 2017 , Mocan and Bali, 2010 ). We define downturns and upturns as periods when the unemployment rate is higher or lower, respectively, than the prior period and zero otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…The second change (March 2010) is closely related to an overall increase in hydrocodone MME (solid blue lines switch to black ones). This regime change is probably due to the economic crisis that commenced in 2008, which has contributed to the increased illegal use of opioid drugs (Azagba et al 2021). The last change (April 2012) is again related to hydrocodone.…”
Section: Applicationsmentioning
confidence: 99%